BAG5 Promotes Alpha-Synuclein Oligomer Formation and Functionally Interacts With the Autophagy Adaptor Protein p62 - Erik L. Friesen; Erik L. Friesen; Yu Tong Zhang; Yu Tong Zhang; Rebecca Earnshaw; Rebecca Earnshaw; Mitch L. De Snoo; Mitch L. De Snoo; Darren M. O’Hara; Darren M. O’Hara; Victoria Agapova; Hien Chau; et al. (Frontiers in Cell and Developmental Biology, 2020)
Molecular chaperones are critical to maintaining intracellular proteostasis and have been shown to have a protective role against alpha-synuclein-mediated toxicity. Co-chaperone proteins regulate the activity of molecular chaperones and connect the chaperone network to protein degradation and cell death pathways. Bcl-2 associated athanogene 5 (BAG5) is a co-chaperone that modulates proteostasis by inhibiting the activity of Heat shock protein 70 (Hsp70) and several E3 ubiquitin ligases, resulting in enhanced neurodegeneration in models of Parkinson’s disease (PD). Here we identify a novel interaction between BAG5 and p62/sequestosome-1 (SQSTM1), suggesting that BAG5 may bridge the chaperone network to autophagy-mediated protein degradation. We found that BAG5 enhanced the formation of pathogenic alpha-synuclein oligomers and regulated the levels and subcellular distribution of p62. These results extend the role of BAG5 in alpha-synuclein processing and intracellular proteostasis.